Methodology for measuring N2 fixation in detached roots of tropical forage grasses - Souto, Sebastião M.; Döbereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2014)
Seven laboratory experiments were carried out to develop a new technique for the study of the nitroganase activity (C2H2 reduction) of detached roots of several tropical grasses. The effect of duration of incubation, pO2, multiplication of N2-fixing bacteria, type and periods of sampling were compared. The new method consists of harvesting pieces of roots attached to 10 cm shoots into 3 litres flask full of water, than replacing the water with N2, 3% O2 and 12% C2H2, incubating at room temperature and determining C2H2 reduction rates between 6 and 8 h. The new methodology developed to study nitrogenase activity in 4 of the 5 grasses understimated that obtained in intact soil-plant systems, but the techniques were significantly correlated with each other (r = 0,91**).